Human γδ T Cell Receptor Repertoires in Peripheral Blood Remain Stable Despite Clearance of Persistent Hepatitis C Virus Infection by Direct-Acting Antiviral Drug Therapy - Ravens, Sarina; Hengst, Julia; Schlapphoff, Verena; Deterding, Katja; Dhingra, Akshay; Schultze-Florey, Christian; Koenecke, Christian; Cornberg, Markus; Wedemeyer, Heiner; Prinz, Immo (Frontiers in Immunology, 2018)
Human γδ T cells can contribute to clearance of hepatitis C virus (HCV) infection, but also mediate liver inflammation. This study aimed to understand the clonal distribution of γδ T cells in peripheral blood of chronic HCV patients and following HCV clearance by interferon-free direct acting antiviral drug therapies. To this end, γδ T cell receptor (TCR) repertoires were monitored by mRNA-based next generation sequencing. While the percentage of Vγ9+ T cells was higher in patients with elevated liver enzymes and a few expanded Vδ3 clones could be identified in peripheral blood of 23 HCV-infected non-cirrhotic patients, overall clonality and complexity of γδ TCR repertoires were largely comparable to those of matched healthy donors. Monitoring eight chronic HCV patients before, during and up to one year after therapy revealed that direct-acting antiviral drug therapies induced only minor alterations of TRG and TRD repertoires of Vγ9+ and Vγ9– cells. Together, we show that peripheral γδ TCR repertoires display a high stability 1) by chronic HCV infection in the absence of liver cirrhosis and 2) by HCV clearance in the course of direct-acting antiviral drug therapy.